Decoding blockchain for business : understand the tech and prepare for the blockchain future - Hijfte, Stijn van (Apress, 2020)
Business professionals looking to understand the impact, future, and limitations of blockchain need look no further. This revolutionary technology has impacted business and the economy in unprecedented way within the past decade, and it is only continuing to grow. As a leader in your organization, it is vital that you decode blockchain and optimize all the ways in which it can improve your business. Author of Decoding Blockchain for Business, Stijn Van Hijfte, expertly emphasizes the imperative of professionals in any sector of industry to understand the core concepts and implications of blockchain technology. Cryptocurrencies, cryptotrading, and constantly-changing tax structures for financial systems using blockchain technologies are covered in detail. The last effects of blockchain across specific industries such as media, real estate, finance, and regulatory bodies are addressed with an insightful eye from Van Hijfte. If not properly implemented with care and a foundation of knowledge, blockchain brings risks and uncertainties to a company. Know your technology to be ready for the present and the future, and stay ahead of the curve. Blockchain is here to stay, and Decoding Blockchain for Business is your professional roadmap.